The Dynamic Effects of Public Capital: VAR Evidence for 22 OECD Countries - Christophe Kamps (Kiel Institute for World Economics (IfW), 2004)
The issue of whether government capital is productive has received a great deal of recent attention. Yet, empirical analyses of public capital productivity have been limited to a small sample of countries for which official capital stock estimates are available. Building on a new database that provides internationally comparable capital stock estimates, this paper estimates the dynamic effects of public capital using the vector autoregressive (VAR) methodology for a large set of OECD countries. The empirical results suggest that there is evidence for positive output effects of public capital in OECD countries, but hardly any evidence for positive employment effects.
Keywords: E60; H54; C32; 330; Public capital; VAR model; Cointegration; OECD countries; Infrastruktur; Produktivität; Beschäftigungseffekt; Schätzung; VAR-Modell; OECD-Staaten